Student attitudes towards the application of e-learning in light of the Corona pandemic - Field study at Mohamed Boudiaf University in M’sila - YOUNSI, AISSA; MOUSSAOUI, OUMESSAAD (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The current study aimed to identify the trends of students at the University of Messila towards the application of e-learning in light of the Corona pandemic. The study also sought to answer the following questions: - What are the attitudes of M'sila University students towards applying e-learning in light of the Corona pandemic? - Are there statistically significant differences in the attitudes of M'sila University students towards applying e-learning in light of the Corona pandemic, according to the gender variable? - Are there statistically significant differences in the attitudes of the students of the University of Messila towards the application of e-learning in light of the delinquency according to the variable of the academic level (Bachelor-Master)? To answer these questions, we relied on the descriptive and analytical method, using a scale prepared by Abdul Qadir bin Obaid Al-Hamiri to verify its psychometric properties. It was applied to a sample of (65) students at the University of Messila, and the study reached the following results: - The attitudes of the students of Mohamed Boudiaf University in Al-Masila towards the application of e-learning in light of the Corona delinquency are supportive. - There are no statistically significant differences in the attitudes of M'sila University students towards the application of e-learning according to the gender variable (male-female);There are no statistically significant differences in the attitudes of the students of the University of M'sila towards the application of e-learning according to the educational level variable (Bachelor's degree- Master).